How to navigate climate security and resilience in the Sahel: From fragility to stability - Sarzana, Carolina; Goldberg, Mark Leon; Sib, Ollo; Doenhert, Federico (2024)
Today’s episode is produced in partnership with the CGIAR Research Initiative on Fragility, Conflict, and Migration for a series that examines what works to improve the well-being of people in Fragile and Conflict Affected Settings. CGIAR is a global partnership that unites international organizations engaged in research about food security. We are calling this series “From Fragility to Stability” and in today’s episode we hold a roundtable discussion with three experts about Climate Security and Resilience in the Sahel.